Análise de desempenho de tubos capilares como dispositivos de expansão em sistemas de ar-condicionado no contexto do índice de desempenho de resfriamento sazonal - Garcia, Guilherme Kley (Universidade do Vale do Rio dos Sinos, 2024)
The Brazilian Labeling Program (PBE) changed the method air conditioners are classified starting in 2023, moving away from the Coefficient of Energy Efficiency (CEE) and adopting the Seasonal Cooling Performance Factor (SCPF). This study aimed to evaluate the performance of capillary tubes as expansion devices in variable refrigerant flow refrigeration systems operating with R-32 refrigerant. To achieve this, a numerical model was developed using the Engineering Equation Solver (EES) software, where the performance of the refrigeration cycle and its main components: compressor, condenser, capillary tube and evaporator were evaluated. This model was compared to a physical model whose results were measured in a calibrated calorimeter chamber. Analyses were conducted at full capacity with an outdoor temperature of 35°C and partial capacity at outdoor temperature of 29°C. It was observed that for each test condition, a different capillary tube specification is capable of extracting the best efficiency results from the system. In the full load test, the smallest capillary tube achieved the best energy efficiency, while at partial load, longer capillary tubes allow the system to operate at lower compressor frequencies, resulting in higher efficiency at this point. Thus, it can be observed that a system that could operate with an idealized capillary tube for each of the test conditions could reduce seasonal consumption by up to 2%.
Keywords: Condicionadores de ar; Modelo numérico; Desempenho sazonal; Tubos capilares; Air conditioning systems; Numerical model; Seasonal performance; Capillary tubes; ACCNPQ::Engenharias::Engenharia Mecânica